2020
DOI: 10.3390/ijerph17051574
|View full text |Cite
|
Sign up to set email alerts
|

Hydrilla verticillata–Sulfur-Based Heterotrophic and Autotrophic Denitrification Process for Nitrate-Rich Agricultural Runoff Treatment

Abstract: Hydrilla verticillata-sulfur-based heterotrophic and autotrophic denitrification (HSHAD) process was developed in free water surface constructed wetland mesocosms for the treatment of nitrate-rich agricultural runoff with low chemical oxygen demand/total nitrogen (C/N) ratio, whose feasibility and mechanism were extensively studied and compared with those of H. verticillata heterotrophic denitrification (HHD) mesocosms through a 273-day operation. The results showed that the heterotrophic and autotrophic denit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…It can be seen from Figure 7a that the denitrification process could be divided into two phases, i.e., the start-up phase (phase I, 1-11 d) and the stable phase (phase II 11-27 d). In phase I, the nitrate removal by denitrification fluctuated due to the acclimation of microorganisms, which was similar to the research results of Hang et al [33]. Initially, the agricultural wastes released abundant soluble and small molecular organics for the denitrification process, but different nitrate removal performance was achieved because of the different amounts and biodegradability of the carbon sources.…”
Section: Denitrification Performancesupporting
confidence: 83%
“…It can be seen from Figure 7a that the denitrification process could be divided into two phases, i.e., the start-up phase (phase I, 1-11 d) and the stable phase (phase II 11-27 d). In phase I, the nitrate removal by denitrification fluctuated due to the acclimation of microorganisms, which was similar to the research results of Hang et al [33]. Initially, the agricultural wastes released abundant soluble and small molecular organics for the denitrification process, but different nitrate removal performance was achieved because of the different amounts and biodegradability of the carbon sources.…”
Section: Denitrification Performancesupporting
confidence: 83%
“…The results of the research showed that the vegetative reproductive structures of hydrilla (tuber and rhizome parts) were able to store carbohydrates (Shi et al, 2021;Fuad et al, 2013;Safitri et al, 2019;Shrivastava dan Sudhakar, 2021). It was also stated that hydrilla contained 3.29% nitrogen (N₂), 0.52% phosphorus (P₂O₅), and 6.34% potassium oxide (K₂O), in which nitrogen, phosphorus, and potassium are macro elements needed by plants in large quantities to grow and develop (Jain dan Kalamdhad, 2019;Hang, et al, 2019;Hang, et al, 2020). It was stated by Jain and Kalamdhad (2018a) that in the hydrilla decomposition process, a denitrification process occurs, namely the reduction of nitrate to nitrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies compared the autotrophic denitrification process performance with the combined heterotrophic-autotrophic process to remove nitrate from agriculture wastewater and showed that the combined process could be more efficient in nitrate removal, and was more stable than the single process of autotrophic denitrification [21] .…”
Section: Introductionmentioning
confidence: 99%